Primary and Secondary Prevention of Obesity - Aleksandra Kiełczewska; Grzegorz Szcześniak; Anna Kiełczewska (Journal of Education, Health and Sport)
Introduction and purpose: Obesity is a persistent and recurring chronic condition marked by an excessive accumulation of body fat, which can deteriorate health, heighten the risk of complications, and shorten life expectancy.This review provides a comprehensive overview of the primary and secondary prevention of obesity, with a focus on interventions and strategies.